Haplotype-resolved genome of diploid ginger (Zingiber officinale) and its unique gingerol biosynthetic pathway. (5th August 2021) - Li, Hong-Lei; Wu, Lin; Dong, Zhaoming; Jiang, Yusong; Jiang, Sanjie; Xing, Haitao; Li, Qiang; Liu, Guocheng; Tian, Shuming; Wu, Zhangyan; Wu, Bin; Li, Zhexin; et al.
Abstract: Ginger ( Zingiber officinale ), the type species of Zingiberaceae, is one of the most widespread medicinal plants and spices. Here, we report a high-quality, chromosome-scale reference genome of ginger 'Zhugen', a traditionally cultivated ginger in Southwest China used as a fresh vegetable, assembled from PacBio long reads, Illumina short reads, and high-throughput chromosome conformation capture (Hi-C) reads. The ginger genome was phased into two haplotypes, haplotype 1 (1.53 Gb with a contig N50 of 4.68 M) and haplotype 0 (1.51 Gb with a contig N50 of 5.28 M). Homologous ginger chromosomes maintained excellent gene pair collinearity. In 17, 226 pairs of allelic genes, 11.9% exhibited differential expression between alleles. Based on the results of ginger genome sequencing, transcriptome analysis, and metabolomic analysis, we proposed a backbone biosynthetic pathway of gingerol analogs, which consists of 12 enzymatic gene families, PAL, C4H, 4CL, CST, C3 ' H, C3OMT, CCOMT, CSE, PKS, AOR, DHN, and DHT . These analyses also identified the likely transcription factor networks that regulate the synthesis of gingerol analogs. Overall, this study serves as an excellent resource for further research on ginger biology and breeding, lays a foundation for a better understanding of ginger evolution, and presents an intact biosynthetic pathway for species-specific gingerol biosynthesis.